Downregulation of S100 calcium-binding A4 (S100A4) ameliorates hepatic fibrosis via regulating Wnt/β-catenin signaling pathway - Chixian Zhang; Kai Bai; Dexu Li (European Journal of Histochemistry)
S100 calcium-binding protein A4 (S100A4), a fibrosis-associated calcium-binding protein, has been implicated in fibrotic progression across multiple organs. Activation of the Wnt/β-catenin signaling pathway is a critical driver of hepatic fibrosis, yet the mechanistic role of S100A4 in this context remains poorly defined. This study investigated the regulatory role of S100A4 in hepatic fibrosis in vitro and in vivo. Hepatic stellate cells (HSCs) were treated with TGF-β to induce fibrotic activation, and S100A4 expression was silenced using shRNA. A carbon tetrachloride (CCl₄)-induced murine hepatic fibrosis model was employed for in vivo validation. Fibrotic markers, including collagen I, fibronectin, and α-smooth muscle actin (α-SMA), were assessed via qRT-PCR, Western blotting, immunofluorescence, and immunohistochemistry. Liver histopathology and function were evaluated using Masson trichrome staining, hematoxylin-eosin staining, and serum ALT/AST assays. In vitro experiments demonstrated that TGF-β treatment upregulated S100A4 expression in HSCs, while S100A4 silencing suppressed HSC activation, extracellular matrix (ECM) deposition, and Wnt/β-catenin signaling. In vivo, S100A4 downregulation attenuated CCl₄-induced hepatic fibrosis, reduced collagen accumulation, improved liver histology, and normalized serum ALT/AST levels. These findings indicate that S100A4 promotes hepatic fibrosis by activating the Wnt/β-catenin pathway, highlighting its potential as a therapeutic target.